Cranial Ultrasonography—Standards in Diagnosis of Intraventricular Hemorrhage and Ventricular Dilatation in Premature Neonates - Adriana Mihaela Dan; Diana Iulia Vasilescu; Ion Dragomir; Sorin Liviu Vasilescu; Diana Voicu; Monica Mihaela Cîrstoiu (Children)
Intraventricular hemorrhage (IVH) is a common complication encountered in extremely-low-birth-weight (ELBW) and very-low-birth-weight (VLBW) premature babies. The neurologic outcome of these patients is influenced by the magnitude of the hemorrhagic process that damages the involved anatomic structures but also by the impaired circulation of cerebrospinal fluid (CSF) through the ventricular system, leading to posthemorrhagic ventriculomegaly (PHVM). Cranial ultrasound (CUS) performed by neonatologists (point-of-care ultrasound—POCUS) facilitates the early diagnosis of IVH and PHVM and can objectively quantify structural alterations. Our aim was to identify the best sonographic criteria to follow-up with ventricular dilatation and predict the need for neurosurgery and neurologic deterioration. We performed a literature review in search of the most relevant ventricular measurements considered by neurosurgeons, neonatologists, and pediatric neurologists to reflect the risk of white matter injury and high intracranial pressure (HIP), thus anticipating neurologic developmental impairment (NDI). The tridimensional picture of ventricular dilatation is best captured if more than one index (ventricular index and anterior horn width) or ratio (Evans ratio, fronto-occipital horn ratio, and fronto-temporal horn ratio) is used. Conclusions: If performed using the correct protocol, serially and comprehensively, CUS is an indispensable tool for the diagnosis and follow-up of neurologic complications of preterm babies, and it can make a difference in guiding adequate intervention and improving long-term developmental outcomes.